2003
DOI: 10.1046/j.1365-2885.2003.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

The comparative serum disposition kinetics of subcutaneous administration of doramectin, ivermectin and moxidectin in the Australian Merino sheep

Abstract: This study evaluates the comparative serum disposition kinetics of injectable formulations of doramectin (DRM), ivermectin (IVM) and moxidectin (MXD) in Australian Merino sheep. Thirty-six, 2-year-old sheep were allocated by weight into six groups of six animals. Animals in each group received 200 microg/kg of DRM, MXD, IVM or a combination of two of these drugs by subcutaneous (s.c.) injection. Blood was collected at designated intervals (between 1 h and 40 days after treatment) and the serum analysed by high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
2
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 35 publications
5
21
2
1
Order By: Relevance
“…The observed peak plasma concentration (C max ) observed in sheep in this study is lower than that reported after subcutaneous administration of 0.2 mg/kg by Barber and colleagues (2003); it is higher than that obtained by Cerkvenik and colleagues (2002). The AUC, which refers to the extent of absorption, is equivalent to that reported previously in sheep (Cerkvenik et al, 2002;Barber et al, 2003). The AUC values observed suggest that the pharmacokinetics of ivermectin in sheep is independent of breed.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The observed peak plasma concentration (C max ) observed in sheep in this study is lower than that reported after subcutaneous administration of 0.2 mg/kg by Barber and colleagues (2003); it is higher than that obtained by Cerkvenik and colleagues (2002). The AUC, which refers to the extent of absorption, is equivalent to that reported previously in sheep (Cerkvenik et al, 2002;Barber et al, 2003). The AUC values observed suggest that the pharmacokinetics of ivermectin in sheep is independent of breed.…”
Section: Discussionsupporting
confidence: 81%
“…Many pharmacokinetic studies following different routes of administration of ivermectin in sheep have been performed (Atta and Abo-Shihada, 2000;Cerkvenik et al, 2002;Echeverria et al, 2002;Barber et al, 2003;Molento et al, 2004). However, there remains a lack information about this endectocide in African breeds.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy sheep administered 200 µg of ivermectin/kg, SC, the value of C max calculated by other authors [8][9][10][11]15,17,26 ranges from 12 to 35 ng/mL. Results of the study reported here (mean ± SD, 19.55 ± 5.03 ng/mL) are similar to results in another study 15 but are lower than most of the values calculated by other authors.…”
Section: Discussionsupporting
confidence: 75%
“…The C max values for doramectin (36.3 ng ml −1 ) and moxidectin (37.5 ng ml −1 ) were equivalent to those reported by Lanusse et al (1997) in cattle (37.5 and 39.4 ng ml −1 , respectively). These values are higher than those reported for sheep (Atta and AboShihada 2000;Barber et al 2003) and goats (Escudero et al 1999). The t max and MRT values for both drugs are also equivalent to those reported for cattle (Lanusse et al 1997).…”
Section: Resultscontrasting
confidence: 38%